CT Appearance Pattern After Stereotactic Body Radiation Therapy Predicts Outcomes in Early-Stage Non-Small-Cell Lung Cancer - Yang, Yan; Li, Gaohua; Li, Shuyuan; Wang, Yuanhang; Zhao, Yanbo; Dong, Baiqiang; Wang, Jin; Zhu, Ruiwu; Chen, Ming (Frontiers in Oncology, 2021)
Backgrounds: Computed tomography (CT) appearance pattern after lung tumor stereotactic body radiation therapy(SBRT) might predicts survival. This study aimed to investigate the correlation between CT appearance pattern after SBRT and outcomes in patients with early-stage non-small-cell lung cancer (NSCLC). Methods: Clinical data of inoperable patients with early-stage NSCLC undergoing SBRT were retrospectively analyzed from 2012 to 2015 at the Zhejiang Cancer Hospital. Follow-up CT scans at one month after SBRT were scored, and the relationship between CT appearance pattern and patient’s survival outcomes was analyzed. Results: A total of 173 patients with early-stage lung cancer treated with SBRT were analyzed. One month after SBRT, diffuse consolidation was seen in 17 patients, patchy consolidation in 28 patients, diffuse ground-glass opacity (GGO) in 10 patients, and patchy GGO in 22 patients. The survival time was significantly longer in the “no evidence of increased density” group compared with the “consolidation or GGO” group [2-year overall survival (OS) rate, 96.1% vs 89.3%; hazard ratio (HR), 0.36; 95% confidence interval (CI), 0.16–0.85; P = 0.015]. A similar trend was found in the progression-free survival (PFS) analysis (2-year PFS rate, 91.3% vs 85.0%; HR, 0.35; 95% CI, 0.13–0.95; P = 0.015) and distant metastasis free survival(DMFS) (2-year DMFS rate, 93.3% vs 87.1%; HR, 0.41; 95% CI, 0.20–0.86; P = 0.031). However, no significant difference was found in recurrence-free survival between the two groups (P = 0.212). Conclusions: One month after SBRT, the radiological change “no evidence of increased density” was prevalent. The OS, PFS, and DMFS were significantly longer in the “no evidence of increased density” group compared with the “consolidation or GGO” group. Further studies are needed to validate these findings.